Method for producing ethanol by fermenting glucose and xylose through mixed bacteria of pichia stipitis and zymomonas mobilis - WU BO; WANG YANWEI; HE MINGXIONG; ZHU QILI; TAN FURONG; SUN LINGLING (2021)
The invention discloses a method for producing ethanol by fermenting glucose and xylose through mixed bacteria of pichia stipitis and zymomonas mobilis, and belongs to the technical field of microbial fermentation, preferably, Scheffersomyces stipitis CICC1960 and Zymomonas mobilis 8b are simultaneously inoculated into a culture medium containing glucose and xylose according to the ratio of 1: 3 for shaking table fermentation, the phenomenon of carbon metabolism inhibition is greatly relieved, and the glucose and xylose can be consumed at the same time; the final xylose utilization amount and the ethanol fermentation concentration of mixed fermentation are respectively improved by 188.99% and 48.37% compared with those of S.stipitis CICC1960 single-bacterium fermentation, and are respectively improved by 5.52% and 6.52% compared with those of Z.mobilis 8b single-bacterium fermentation; the fermentation process is simple to operate and the ethanol fermentation efficiency is high. 本发明公开了一种树干毕赤酵母与运动发酵单胞菌混菌发酵葡萄糖和